Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar pada Materi Penaksiran Hasil Operasi Hitung Bilangan di Kelas IV Sekolah Dasar - Izzatil Mufidah; Syafri Ahmad (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims to determine the effect of the Problem Based Learning model on learning outcomes in the material estimation results of numerical operations in class IV Elementary School. The research design used is Quasi Experimental Design. The population in this study were class IV students of SDN 27 Anak Air. With the simple random sampling technique, the IVC class was obtained as the experimental class and IVB as the control class. Based on the results of data analysis using t-test, obtained tcount = 2.423 and ttable = 1.669 at a significant level of 0.05 and dk = 62. It means tcount> ttable so that Ha is accepted. Therefore, there is a positive and significant effect on the Problem Based Learning learning model on learning outcomes in the material estimation results of numerical operations in class IV Elementary School.